Behavior of a methanol fuel cell in transitory regime - García, María F.; Pilla, Ana S.; Duarte, Marta M.E. (Revista Ciências Exatas, 2009)
The operation of a polymeric electrolyte methanol/air fuel cell connected to a storage tank with anolyte batch recycle is analyzed. When the cell is discharged at constant current, far below the anode reaction limiting current density, the concentration in the tank is found to decrease with time following a lineal variation. At zero time, a high CO2 concentration is detected in the air leaving the cathode compartment, which increased when higher methanol concentration is used in the anode compartment. This effect is associated to the crossover of methanol through the membrane. The amount of CO2 in the air outlet is important, and both this quantity and the crossover flux decrease when methanol concentration diminish in the anolyte. A model derived from electrochemical reactor analysis, that correlates methanol concentration changes in the storage tank, and methanol concentration at the anodic compartment exit with the amount consumed in the cell reaction and the flow through the membrane is developed.